Assessment of Trace Metal Concentrations in Feathers of White-chinned Petrels, Procellaria Aequinoctialis, from the Patagonian Shelf - Seco Pon, Juan Pablo (2012)
Cd, Cr, Cu, Fe, Ni, Pb, and Zn were measured in feathers from male and female White-chinned petrels Procelllaria aequinoctialis accidentally killed in longliners off Argentina in 2005. Cd, Pb, and Ni concentrations in adult feathers were below detection limits regardless of the birds’ sex. Metal concentrations did not vary with sex for Cu, Fe and Zn in feathers of adult birds despite significant differences in body size between males and females. The Cu and Fe concentrations differed significantly between the type of feather within individual birds. The mean concentrations of metals determined here were within the range of concentrations reported in feather tissues of other related Procellariiformes species from different biogeographic areas. However, the concentrations of Cr were similar to those reported for other petrels from polluted areas of the North Pacific. Thus, it appears likely that levels of pollution in Patagonia may not be as negligible as previously thought for some trace metals.